Exploration of The Preservation of Kamali Baadia Museum and The Philosophical Value of The Dignity of The Seven Buton Sultanes - Ramadhani, Rahmi; Putra, Zulfikar; Sopiandy, Dede; Anastasia, Anastasia (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
The Kamali Baadia Museum in Bau-Bau City serves as a key institution in the preservation of cultural heritage and public education. This study aims to analyze the physical preservation of the museum's buildings and collections and highlight the philosophical values contained in its history. Data collection methods used in this study include interviews with museum managers, direct observation of collections and buildings, and review of related documentation. The study results indicate that this museum serves as a place to store artifacts and as an educational vehicle that encourages public awareness of the importance of cultural and historical identity. The concept of Martabat Tujuh reflects the harmony between Islamic teachings and the local culture of the Buton community. Martabat Tujuh emphasizes universal values such as justice, humanity, and local wisdom, which are the basis for social and cultural interactions in the region. Community involvement in the process of preserving cultural heritage is the key to success in maintaining the authenticity of local culture. Through the promotion of the values of Martabat Tujuh, the Kamali Baadia Museum strengthens the community's sense of ownership of their cultural heritage and supports the balance between worldly and afterlife needs. This study provides important insights into the role of museums in educating the public and internalizing cultural values as part of a broader national identity